Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1021/acsami.6b06081
|View full text |Cite
|
Sign up to set email alerts
|

MoS2 Quantum Dots with a Tunable Work Function for High-Performance Organic Solar Cells

Abstract: An efficient hole extraction layer (HEL) is critical to achieve high-performance organic solar cells (OSCs). In this study, we developed a pinhole-free and efficient HEL based on MoS quantum dots (QDs) combined with UV-ozone (UVO) treatment. The optophysical properties and morphology of MoS QDs and their photovoltaic performance are investigated. The results showed that MoS QDs can form homogeneous films and can be applied as an interfacial layer not only for donors with shallow highest occupied molecular orbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 49 publications
0
62
0
Order By: Relevance
“…So far, those researched solvents can be classified as water phase (e.g., sulfuric acid, surfactants aqueous solution), and organic solvents phase (e.g., N, N‐dimethylformamide (DMF), N‐methyl‐2‐pyrrolidone (NMP), isopropyl alcohol (IPA), and ethylene glycol) . For example, a sulfuric acid‐assisted ultrasonic route was provided for controllable‐size MoS 2 QDs with excellent PL properties through exfoliating and cutting bulk MoS 2 powder . Combining the sonication and solvothermal treatments, MoS 2 and WS 2 QDs with monolayer thickness were synthesized from their bulk crystals .…”
Section: Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…So far, those researched solvents can be classified as water phase (e.g., sulfuric acid, surfactants aqueous solution), and organic solvents phase (e.g., N, N‐dimethylformamide (DMF), N‐methyl‐2‐pyrrolidone (NMP), isopropyl alcohol (IPA), and ethylene glycol) . For example, a sulfuric acid‐assisted ultrasonic route was provided for controllable‐size MoS 2 QDs with excellent PL properties through exfoliating and cutting bulk MoS 2 powder . Combining the sonication and solvothermal treatments, MoS 2 and WS 2 QDs with monolayer thickness were synthesized from their bulk crystals .…”
Section: Synthesismentioning
confidence: 99%
“…The photovoltaic performance of MoS 2 QDs were investigated and the results showed that the homogeneous films of MoS 2 QDs with desired photovoltaic performance could be applied not only as donors with shallow highest occupied molecular orbital (HOMO) but also for those with deep HOMO energy levels after UV‐ozone treatment. Meanwhile, the stability of solar cells based on MoS 2 QDs is remarkably improved, showing their significant potential as an efficient HEL for high‐performance organic solar cells (Figure b) …”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations